The challenges of mainstream deammonification process for municipal used water treatment - Xu, Guangjing (2015)
The deammonification process combining partial nitritation and anaerobic ammonium oxidation has been considered as a viable option for energy-efficient used water treatment. So far, many full-scale sidestream deammonification plants handling high-ammonia used water have been in successful operation since Anammox bacteria were first discovered in the 1990s. However, large-scale application of this process for treating municipal used water with low ammonia concentration has rarely been reported. Compared to the sidestream deammonification process, the mainstream deammonification process for municipal used water treatment faces three main challenges, i.e., (i) high COD/N ratio leading to denitrifiers outcompeting Anammox bacteria, (ii) numerous difficulties in selective retention of ammonia-oxidizing bacteria (AOB) over nitrite-oxidizing bacteria (NOB), and (iii) sufficient accumulation of Anammox bacteria. Therefore, this paper attempts to provide a detailed analysis of these challenges and possible solutions towards sustainable mainstream deammonification process.